Competing risks for reliability analysis using Cox’s model - Mohamed Elfaki, Faiz Ahmed; Daud, Isa; Ibrahim, Nor Azowa; Abdullah, M. Y.; Usman, Mustofa (Emerald Group Publishing Limited, 2007)
Purpose – Cox’s model with Weibull distribution and Cox’s with exponential distribution are the most important models in reliability analysis. This paper seeks to show that, with a large sample size based on expectation maximization (EM) algorithm, both models give similar results.